Integration of e‐Health Tools Into Face‐to‐Face Psychotherapy for Borderline Personality Disorder: A Chance to Close the Gap Between Demand and Supply?. Issue 8 (24th July 2015) - Fassbinder, Eva; Hauer, Andrea; Schaich, Anja; Schweiger, Ulrich; Jacob, Gitta A.; Arntz, Arnoud; McMain, Shelley F.
<x xml:space="preserve">Abstract</x> Borderline personality disorder (BPD) is a severe, highly prevalent mental disorder. Effective psychological treatments for BPD are available. However, most patients do not receive evidence‐based treatments partly because of high treatment delivery costs and lack of specialized therapists. By integrating specialized e‐health tools into BPD‐specific treatments, treatment intensity can be increased, frequency of face‐to‐face sessions and burden for psychotherapists can be reduced, and implementation of new skills and experiences in the everyday life of these patients can be promoted. This bears great potential to increase the availability of evidenced‐based psychotherapy for BPD patients and close the gap between demand and supply. In this article we present such an innovative e‐health tool, priovi, which has been developed for schema therapy. The concept and application of priovi are described and illustrated with a case example.